The impact of low emission zones on particulate matter concentration and public health - Christiane Malina; Frauke Fischer (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2014)
A common policy for reducing particulate matter concentrations in the European Union is the introduction of Low Emission Zones (LEZs), which may only be entered by vehicles meeting predefined emission standards. This paper examines the effectiveness of LEZs for reducing PM10 levels in urban areas in Germany and quantifies the associated health impacts from reduced air pollution within the zones. We employ a fixed effects panel data model for daily observations of PM10 concentrations from 2000 to 2009 and control, inter alia, for local meteorological conditions and traffic volume. We apply the regression outputs to a concentration response function derived from the epidemiological literature to calculate associated health impacts of the introduction of LEZs in 25 German cities with a population of 3.96 Mio. Associated uncertainties are accounted for in Monte-Carlo simulations. It is found that the introduction of LEZs has significantly reduced inner city PM10 levels. We estimate the total mean health impact from reduced air pollution in 2010 due to the introduction of stage 1 zones to be ~700 Mio. EUR in the 25 LEZ-cities in the sample, whereas total mean health benefits are ~2.4 Billion EUR for the more stringent stage 2 zones when applied to the same cities.
Keywords: 330; Environmental policy; Germany; low emission zones; road transport; particulate matter; health effects